Electric field variations across DLPFC targeting methods in TMS therapy for Alzheimer’s disease - Nianshuang Wu; Yuxuan Shao; Zhen Wu; Shuxiang Zhu; Penghao Wang; Ziyan Zhu; Cheng Zhang; Changzhe Wu; Xiaolin Huo; Hua Lin; Guanghao Zhang (NeuroImage: Clinical, 2025)
Background: The dorsolateral prefrontal cortex (DLPFC) is crucial for cognitive control and a primary target for transcranial magnetic stimulation (TMS) in Alzheimer’s disease (AD). However, understanding the distribution of TMS-induced electric field (E-field) across different targeting methods remains limited, as does its relationship to therapeutic outcomes. Objective: This study assesses differences in TMS-induced E-field using functional versus anatomical targeting methods for DLPFC stimulation. Methods: Functional and anatomical targets were identified in 30 (11 M/19F) AD patients and 30 (13 M/17F) age-matched healthy controls (HCs) using T1 and fMRI data. E-field characteristics, including magnitude (EROI) and normal component (E⊥), were calculated via SimNIBS software for comparisons across stimulation targets. Results: Functional targeting showed greater spatial dispersion compared to anatomical targeting in both groups. Significant E-field differences were observed between the functional target and adjacent anatomical regions when the coil was positioned over the functional target in both groups. Optimal coil orientation exhibited directional specificity: parallel alignment with the LOI E-field produced higher field intensity in the functional target compared to the anatomical target (AD patients: P < 0.001; HCs: P = 0.052), while perpendicular orientation maintained functional stability with reduced anatomical interference (both groups: P < 0.001). And significant variations in E-field ratios were observed across coil orientations. Conclusion: This study reveals key E-field disparities across DLPFC targeting approaches and establishes coil orientation optimization as a critical strategy to improve TMS precision, offering actionable insights for developing personalized protocols in AD therapy that may enhance treatment efficacy while minimizing adverse effects.